Critical Discourse on Press Contribution to NTT Good Local Governance - Yonas Klemens Gregorius Dori Gobang; Adrianus Nabung; Marianus Mantovanny Tapung (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2022)
The contribution of local media in articulating its control function to restore people’s rights and encourage the implementation of good local governance cannot be separated from the professionalism and critical support of the media crew. This is because the relationship between local media and regional authorities is still prone to conflict, complex, and bound by certain emotional-cultural aspects. Using critical discourse analysis, this study examines specifically the editorial texts of two local mainstream newspapers, Flores Pos and Pos Kupang, related to some strategic issues, especially corruption issues, within the Provincial Government of NTT. The study found that the reality of local media can be co-opted by the interests of media owners and local governments. It also confirms that local media are not absolutely neutral or interest-free. The neutrality of local mass media is also influenced by the dominance of media owners who have power relations with regional authorities.